ANALISIS PENGGUNAAN BENFORD’S LAW DALAM PERENCANAAN AUDIT DI DIREKTORAT JENDERAL BEA DAN CUKAI CABANG KOTA LHOKSEUMAWE - Murhaban, Murhaban; Jufrizal, Jufrizal (Department of Accounting, Faculty of Economics & Business, 2017)
This study aims to analyze the use of Benford's Law in Audit Planning at the Directorate General of Customs and Excise, Lhokseumawe City. The data used in this study are secondary data obtained directly from the Directorate General of Customs and Excise, Lhokseumawe City in 2015-2017. Data analysis methods used in this study are First Digits, Second Digits, and Three Digits. The results show that Benford's Law requirements analysis meet the requirements, and from the results of the Benford's Law data analysis, there are differences in the actual frequency data patterns with the Benford's Law frequency pattern, and also from the differences in frequency patterns that show that Benford's Law is effective and could be used to detect predictions of audit findings appropriately.